An investigation of age dependency in Dutch and Chinese values for EQ-5D-Y - Essers, Brigitte; Wang, Pei; Stolk, Elly; Jonker, Marcel F.; Evers, Silvia; Joore, Manuela; Dirksen, Carmen (Frontiers in Psychology, 2023)
Aims: The primary aim was to explore age-dependency of health state values derived via trade-offs between HRQoL and life years in a discrete choice experiment (DCE). A secondary aim was to explore if people weigh life years and HRQOL differently for children, adolescents, adults and older adults. Methods: Participants from the general population of the Netherlands and China first completed a series of choice tasks offering choices between two EQ-5D-Y states with a given lifespan. The choice model captured the value of a year in full health, disutility determined by EQ-5D-Y, and a discount rate. Next, they received a slightly different choice task, offering choices between two lives that differed in HRQoL and life expectancy but produced the same number of QALYs. Participants were randomly assigned to fill out the survey for three or four age frames: a hypothetical person of 10, 15 ,40, and 70 year (the last one only applicable for China) to allow age dependency of the responses to be explored. Results: 1,234 Dutch and 1,818 Chinese people administered the survey . Controlling for time preferences, we found that the agreement of health state values for different age frames was generally stronger in the Netherlands than the agreement in China. We found no clear pattern of differences for the QALY composition in both samples. The probability distribution over response options varied most when levels for lifespan or severity were at the extremes of the spectrum. Conclusion/discussion: The magnitude and direction of age-effects in values seemed dimension- and country specific. In the Netherlands, we found a few differences in dimension specific weights elicited for 10- and 15-year-olds compared to 40-year-olds, but the overall age-dependency of values was limited. Stronger age-dependency of values was observed in China, where values for 70-year-olds differed strongly from the values for other ages. The appropriateness of using existing values beyond the age range for which the values were measured needs to be evaluated in the local context.